2008
DOI: 10.1051/parasite/2008151053
|View full text |Cite
|
Sign up to set email alerts
|

Hypobaric hypoxia-related impairment of pulmonary surfactant proteins A and D did not favourPneumocystis cariniiFrenkel 1999 growth in non-immunocompromised rats

Abstract: Summary :It has been suggested that patients with pulmonary surfactant impairment are more susceptible to Pneumocystis infection than healthy controls. Owing the fact that most patients with pulmonary surfactant impairment also suffer from hypoxia, we explored the effect of intermittent hypobaric hypoxia conditions on the ability of non-immunocompromised rats infected by endotracheal route with P. carinii to clear the infection from their lungs. Control rats, inoculated or not with P. carinii, were maintained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…In nonimmunocompromised laboratory rats, hypobaric hypoxia weakened host immune mechanisms and significantly impaired the surfactant composition. Such changes were not enough, however, to favor Pneumocystis growth or to inhibit Pneumocystis clearing from their lungs (95).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In nonimmunocompromised laboratory rats, hypobaric hypoxia weakened host immune mechanisms and significantly impaired the surfactant composition. Such changes were not enough, however, to favor Pneumocystis growth or to inhibit Pneumocystis clearing from their lungs (95).…”
Section: Discussionmentioning
confidence: 99%
“…The almost exponential decline of the atmospheric pressure is accompanied by a parallel decline of the oxygen pressure in the inspired air, which induces hyperventilation. Thus, altitude could directly impact on respiratory physiology and host defense mechanisms (95) and indirectly act on the development of Pneumocystis organisms in the alveolar microenvironment. These aspects were not explored in bats.…”
Section: Discussionmentioning
confidence: 99%
“…Specific properties of SP‐A include direct antimicrobial activity, non‐immune opsonization, and/or modulation of the host immune response (Santo and Kuroki 2004). We and other investigators have shown that immunosuppressed SP‐A knockout (KO) mice develop higher levels of PCP than immunosuppressed wild‐type (WT) mice (Atochina et al 2004a; Linke et al 2001, 2005; Vives et al 2008). Upon removal of the immunosuppression, SP‐A does not appear to affect the clearance of P. murina , but does alter the host immune response (Linke et al 2006a, b).…”
mentioning
confidence: 98%